Antibiotic prophylaxis. Issue 11 (November 2015) - Hall, Charlotte; Allen, Joanna; Barlow, Gavin
Abstract: Surgical site infection (SSI) is a common postoperative complication which leads to significant morbidity and mortality. The aim of antibiotic prophylaxis is to reduce the incidence of SSI by preventing the development of infection due to colonizing or contaminating organisms at the operative site. It is used as an adjunct to, rather than a replacement for, other evidence-based interventions to prevent wound infection, such as the use of skin antiseptics. The choice of antimicrobial agent(s) used is dependent on how clean the operation is, the operative site (which determines the likely organisms), and a variety of patient factors including the presence of allergies and colonization with resistant organisms such as meticillin-resistant Staphylococcus aureus (MRSA). The practicalities of antibiotic prophylaxis administration are discussed. Not all operations require antibiotic prophylaxis; use of antibiotics in any context, including as prophylaxis, can be associated with adverse effects, specifically an increased risk of Clostridium difficile infection (CDI) and resistance development. Prophylaxis should therefore be used responsibly. This article will address some of the common misconceptions about its use and special patient circumstances requiring deviation from the usual guidance.